RECORD DATA PROCESSING PROGRAM SEHATI CLINICAL APPLICATIONS USING MICROSOFT VISUAL FOXPRO 6.0 - Agung Komarudin; Linda Wahyu Widianti, Skom., MMSI (Jurnal Sistem Informasi, 2004)
Advances in computer technology very rapidly at this time a positive impact on thedevelopment of information technology business world. Work processes that still usethe manual process can be computerized so that the deficiencies and weaknesses thatcan occur in a manual process in minimizing. Scientific writing is about making theprogram record data processing applications using the programming languagesoftware Microsoft Visual FoxPro 6.0.This application program is expected to optimize the performance of the clinic. Thisprogram includes procedures to enter data, add, and change diagnostic data, physiciandata, patient data and procedures is also equipped with printing a report.